Poly-Cross-Linked PEI Through Aromatically Conjugated Imine Linkages as a New Class of pH-Responsive Nucleic Acids Packing Cationic Polymers - Chen, Shun; Jin, Tuo (Frontiers in Pharmacology, 2016)
Cationic polyimines polymerized through aromatically conjugated bis-imine linkages and intra-molecular cross-linking were found to be a new class of effective transfection materials for their flexibility in structural optimization, responsiveness to intracellular environment, the ability to facilitate endosome escape and cytosol release of the nucleic acids, as well as self-metabolism. When three phthalaldehydes of different substitution positions were used to polymerize highly branched low molecular weight polyethylenimine (PEI-1.8K), the product through ortho-phthalimines (named PPOP) showed significantly higher transfection activity than its two tere- and iso-analogues (named PPTP and PPIP). Physicochemical characterization confirmed the similarity of three polyimines in pH-responded degradability, buffer capacity, as well as the size and Zeta potential of the polyplexes formed from the polymers. A mechanistic speculation may be that the ortho-positioned bis-imine linkage of PPOP may only lead to the straight trans-configuration due to steric hindrance, resulting in larger loops of intra-polymer cross-linking and more flexible backbone.